The Attraction Advantage: How Celebrity Charisma Outperforms Expertise in Attitude-Mediated Green Marketing - Irawan, Ari; Zalfaa, Alyaa; Sanawiri, Brillyanes; Agusti, Rosalita Rachma; Iqbal, Mohammad (Universitas Airlangga, 2025)
Objective: This study examines the role of consumer attitudes in the relationship between celebrity endorser credibility (attractiveness, trustworthiness, and expertise) and green purchase intention, with innovativeness as a moderating variable. The research clarifies how these factors impact purchase intention for eco-friendly products, focusing on a green beauty brand. Design/Methods/Approach: This explanatory research utilizes a quantitative approach to analyze relationships between variables. The sample consists of 200 Instagram users. Data was collected via questionnaires and analyzed using SmartPLS software, employing descriptive analysis and path analysis to examine celebrity endorser credibility influence on consumer attitudes and purchasing behavior. The theoretical framework integrates the Source Credibility Model, Theory of Planned Behavior, and Diffusion of Innovations Theory to examine celebrity endorser credibility influence on consumer attitudes and purchasing behavior. Findings: All three dimensions of celebrity endorser credibility, attractiveness, trustworthiness, and expertise, positively and significantly influenced consumer attitudes towards green products. Attitudes towards green products significantly impacted green purchase intentions. Consumer innovativeness negatively moderated the relationship between attitudes and green purchase intentions, indicating that innovative consumers are less influenced by attitudes when making purchasing decisions. Originality/Value: This study disaggregates celebrity credibility dimensions in green marketing contexts, revealing that attractiveness dominates over expertise in driving green purchase intentions through attitude formation. The research uniquely identifies consumer innovativeness as a negative moderator, demonstrating that highly innovative consumers rely less on attitude formation when making green purchase decisions, challenging traditional consumer behavior models. Practical/Policy Implication: Brand managers of green beauty products seeking to increase green purchase intention should prioritize celebrity attractiveness over expertise when selecting endorsers. Marketing practitioners should develop campaigns emphasizing emotional appeal while implementing differentiated strategies for innovative consumers, highlighting product uniqueness rather than traditional environmental benefits.